Infant Nutritional Status of 0-6 Months of Exclusive Breastfeed Due to The Application of Moringa Leaf Extract in Breastfeeding Mothers - Zakaria, Zakaria; Hadju, Veni; Rosmini, Rosmini (Health Notions, 2018)
The objective of this study was to assess the difference between 0-6 months of exclusive breastfeeding status in breastfeeding mothers who received Moringa leaf extract  and Moringa flour. Intervention study with double blind with randomized controlled, implemented in Maros Regency, Sulawesi Selatan Province, Indonesia. Sample was 70 mothers and infants (35 as intervention group and 35 as control group). Material of intervention were Moringa leaf extract and Moringa leaf powder for control group. The data were analyzed using T-test. The results showed that the infants nutritional status based on the Z score of body weight by age (WA) at 4 months of age was significantly different (p = 0.030) and was not significantly different (p = 0.062) at 6 months. Infants nutritional status based on Z score of body length by age (HA) was not significantly different at age 4 and 6 months (p = 0.339 and 0.265).